INSTITUTIONAL EQUILIBRIUM AMONG THE LEGISLATIVE, EXECUTIVE, AND JUDICIAL BRANCHES: IMPLICATIONS FOR THAI DEMOCRACY - Wisetchai, Shanasuek (Journal of MCU Nakhondhat, 2026)
This research article aims to 1) Analyze the structural imbalance among the legislative, executive, and judicial institutions within the Thai parliamentary system, and 2) Analyze the impacts of the structural imbalance among the legislative, executive, and judicial institutions on Thai democratic governance. The study employs a qualitative research methodology, collecting data through document analysis combined with in-depth interviews with 20 key informants purposively selected from three groups: political science and legal scholars, politicians and members of parliament, and members of the judiciary. The research instruments consisted of a document analysis form and a semi-structured in-depth interview guide. Data were analyzed using content analysis and thematic analysis, with data trustworthiness verified through triangulation. The findings reveal that: 1) The relationship among the three principal institutions exhibits three structural imbalances: the executive’s domination over the legislative process through patronage networks and party discipline; a dual structural paradox that renders the legislature’s oversight function ineffective regardless of whether the executive maintains control over the parliamentary majority; and the expansion of Constitutional Court power without adequate reverse accountability mechanisms. and 2) These imbalances impact Thai democracy in four dimensions: the nullification of the people’s will by unelected institutions; the exercise of executive power without effective institutional oversight; the erosion of the rule of law resulting from the imbalance of power in both directions; and public distrust toward the political system leading to a vicious cycle of instability. The article proposes institutional reform measures including strengthening the independence of the legislature, establishing reverse accountability mechanisms for the judiciary, and reforming the political party system to reduce the influence of patronage networks.